2018
DOI: 10.1109/jlt.2018.2874086
|View full text |Cite
|
Sign up to set email alerts
|

Photodarkening-Induced Phase Distortions and Their Effects in Single-Channel and Coherently Combined Yb-Doped Fiber Chirped Pulse Amplification Systems

Abstract: We use numerical simulations to investigate the effects of photodarkening (PD) on pulse compression and coherent combination following chirped-pulse amplification in Yb-doped fiber amplifiers. Even though we increase the pump power to keep the pulse energy constant, PD degrades the pulses due to phase distortions resulting from heating acting already within a pulse as well as to increased self-phase modulation if the fiber length is optimized for the PD-free fiber at beginning of life. By contrast, in a fiber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
(44 reference statements)
1
2
2
Order By: Relevance
“…However, the phase in the trailing edge of the pulses is smaller than that in the leading edge, by an amount of between 0.6 and 1.3 rad at 0.5 ns. This asymmetry may be caused by energy-related phase effects, which build up during the pulse [9]. In contrast to these experiments, the simulations in [9] showed larger phase in the trailing edge than in the leading edge.…”
Section: Resultscontrasting
confidence: 70%
See 3 more Smart Citations
“…However, the phase in the trailing edge of the pulses is smaller than that in the leading edge, by an amount of between 0.6 and 1.3 rad at 0.5 ns. This asymmetry may be caused by energy-related phase effects, which build up during the pulse [9]. In contrast to these experiments, the simulations in [9] showed larger phase in the trailing edge than in the leading edge.…”
Section: Resultscontrasting
confidence: 70%
“…This asymmetry may be caused by energy-related phase effects, which build up during the pulse [9]. In contrast to these experiments, the simulations in [9] showed larger phase in the trailing edge than in the leading edge. This suggests that the refractive index decreases through the combined effect of energy extraction from the Yb-ions and heat deposition.…”
Section: Resultscontrasting
confidence: 70%
See 2 more Smart Citations
“…By theoretically calculating the thermally-induced mode loss evolution, it showed that the refractive index of the Yb-doped fiber would be changed by the thermo-optic effect, which affected the waveguide structure and altered the bending loss of different modes [24]. Moreover, the phase of the beam could be distorted by PD-induced thermal load [25]. Meanwhile, PD effect would significantly increase the thermal load of the active fiber and aggravate thermally induced refractive index grating, which eventually triggered the occurrence of TMI effect [26].…”
Section: Introductionmentioning
confidence: 99%